Tapering and performance - Coulson, M.
When planning any form of tapering programme I would recommend the following points. The training incorporated into the programme should be reduced in an incremental fashion with a 60-90 per cent reduction in training volume. Training intensities should take the form of high interval work (90% VO2max) with sufficient rest between sets. The frequency of training should be reduced by no more than 20 per cent in order for the swimmers to maintain their 'feel' of the water, and, finally, duration of the taper programme should be decided on an individual basis (because of varying responses to tapers) and last between seven and 21 days.